CBIO-06. MKlp2 INHIBITION AS A NOVEL ANTIMITOTIC FOR GLIOBLASTOMA. (9th November 2020) - Schrock, Morgan; Scarberry, Luke; Stromberg, Benjamin; Torres, Adrian; Chakravarti, Arnab; Venere, Monica; Summers, Matthew
Abstract: Despite innovations in therapy and surgery, glioblastoma remains one of the deadliest tumor types with a 5-year survival rate of approximately 5%. There is a desperate need for new therapeutic strategies to block the growth and survival of glioblastoma. To circumvent toxicities associated with traditional antimitotics, there has been a growing interest in developing therapies that impede mitosis-specific microtubule functions, such as the inhibition of kinesins, mitotic motor proteins that travel along microtubules. Our work with motor kinesin-like protein 2 (MKlp2), in combination with reports from published literature, suggest a previously undescribed role for MKlp2 in early mitosis that would make its inhibition effective at impeding glioblastoma cell growth without neurologic side effects. The objective of this study was to further define this novel function of MKlp2 and to determine the efficacy of MKlp2 inhibition in glioblastoma. Our data indicate that MKlp2 inhibition induced a spindle assembly checkpoint-mediated arrest, suggesting that function of MKlp2 is important for recovery progression to anaphase in addition to its well-known function in late mitosis. In addition, MKlp2 inhibition with a small molecule MKlp2 inhibitor significantly decreased short-term and long-term survival of human glioblastoma patient-derived lines. Furthermore, our data indicate that it is loss of this early mitotic function that is responsible for the anti-proliferative effects caused by MKlp2 inhibition. Ongoing work will continue to delineate the mechanism of MKlp2 in early mitosis and determine the effect of small molecule MKlp2 inhibition in vivo, all the while exploring a new therapeutic strategy for glioblastoma